Exploratory Laparotomy for Severe Dowry-related Spousal Violence Injuries in a Young Woman - Sapkota, Arbin Dev; Bhattarai, Abhishek; Rimal, Sudesha; Shrestha, Roshan; Regmi, Sadikshya; Atreya, Alok (Journal of Nepal Health Research Council, 2025)
This case report highlights the severity of dowry-related intimate partner violence in Terai, Nepal. A 24-year-old married female presented with multiple stab injuries to the abdomen and a cut-throat injury inflicted by her husband under the influence of alcohol due to dissatisfaction with dowry demands. Successful management involved exploratory laparotomy, anterior abdominal wall repair, cholecystectomy, and neck injury repair. However, on the third postoperative day, due to persistent pain and feeding difficulties, the patient was referred to a tertiary care center, where a re-exploratory laparotomy revealed missed diaphragmatic injury and bowel herniation requiring further repair. This case underscores the need for high clinical suspicion and early specialist referral in complex trauma scenarios. It also highlights the role of cultural and societal factors in intimate partner violence and the need for a multidimensional approach involving healthcare, legal, and social services. Keywords: Abdominal trauma; dowry; intimate partner violence; Nepal; stab injury